1999
DOI: 10.1074/jbc.274.11.6957
|View full text |Cite
|
Sign up to set email alerts
|

High Base Pair Opening Rates in Tracts of GC Base Pairs

Abstract: Sequence-dependent structural features of the DNA double helix have a strong influence on the base pair opening dynamics. Here we report a detailed study of the kinetics of base pair breathing in tracts of GC base pairs in DNA duplexes derived from 1 H NMR measurements of the imino proton exchange rates upon titration with the exchange catalyst ammonia. In the limit of infinite exchange catalyst concentration, the exchange times of the guanine imino protons of the GC tracts extrapolate to much shorter base pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
157
0
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(178 citation statements)
references
References 30 publications
13
157
0
8
Order By: Relevance
“…However, we should bear in mind that ξ not only determines the definition of 'open' and 'closed', but also determines the ensemble via Eqs. (5,6). Considering Eq.…”
Section: Denaturation Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we should bear in mind that ξ not only determines the definition of 'open' and 'closed', but also determines the ensemble via Eqs. (5,6). Considering Eq.…”
Section: Denaturation Curvesmentioning
confidence: 99%
“…The sequence specific order is also important. Specific sequences can reveal a high opening rate despite a high fraction of GC base-pairs [6]. Besides the already mentioned UV absorbance experiments, many ingenious techniques have been devised to study the denaturation process and the statistical and dynamical properties of DNA bubbles in general.…”
Section: Introductionmentioning
confidence: 99%
“…Those curves are easy to record experimentally because the UV absorbance of a DNA solution increases drastically when the bases are unstacked, which is [3,4] managed to get some data on the melting process of short DNA sequences, detecting whether they open at one end or by starting with an open bubble in the centre. The kinetics of proton-deuterium exchange for the protons involved in the hydrogen bonds within pairs, coupled with NMR studies to detect the location of the exchanged protons, can also provide partial information on the spatial aspect of DNA fluctuations, at the expense of heavy experiments [5]. Another approach relies on special molecular constructs which attach a fluorophore and a quencher to DNA to detect its local opening at a particular site [6,7].…”
mentioning
confidence: 99%
“…It has been shown that homosequence DNA denatures quite abruptly within a very small temperature interval, whereas heterosequence DNA denatures via a few partial denaturation states [22,38], leading to a denaturation curve (plot of average number of open bp's against temperature) whose shape is highly sensitive to the sequence. The melting and its transition do not only depend on the fraction of strong G-C or A-T bonds, but are also sequence specific [39]. This phenomena has been recently suggested as an application for DNA sequencing [40].…”
Section: Denaturation Of Diblock Dnamentioning
confidence: 99%